Adaptive approach-based assessment of a heritage residential complex in southern Spain for improving comfort and energy efficiency through passive strategies: A study based on a monitored flat. (15th August 2019) - Blázquez, Teresa; Ferrari, Simone; Suárez, Rafael; Sendra, Juan José
Abstract: The energy retrofitting of residential stock is not always straightforward where heritage protected housing is concerned. In southern Europe, many examples built under the Modern Movement codes are now obsolete in terms of energy efficiency. The aim of this paper is to assess the potential for improvement of comfort conditions and energy efficiency in Mediterranean heritage residential buildings, through the incorporation of passive strategies in keeping with preserving heritage values. Long-term monitoring and field tests in representative flats of the case-study building were carried out and, focusing on a single example, adaptive comfort equations were used to assess results. The passive strategies considered are the thermal isolation of the air cavities of walls, changing window frames, optimizing window glazing, and setting up regular mechanical ventilation rates for indoor air changes. Although simulation results generally predict a better energy performance after testing retrofit strategies, the potential decrease in energy demand is more noticeable than the potential improvement in comfort conditions. Highlights: The improvement of comfort and energy efficiency in a heritage building is assessed. Long-term monitoring and field tests were carried out in representative flats. Passive strategies in keeping with preserving heritage values were examined. Adaptive comfort equations were used to assess results focusing on one flat. Energy efficiency improvements are more noticeable than those of comfort conditions.